Evaluation of Nutrition Education at Senior High Schools in Mamuju Regency West Sulawesi - Nurbaya, Nurbaya; Najdah, Najdah (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2024)
Abstract Introduction: The 2018 Basic Health Research showed a high prevalence of anemia (32%), Chronic Energy Deficiency (36.3%), and overweight and obesity (16.0%) among adolescents. Nutrition education is crucial to be taught to adolescents from an early age. However, there is a lack of research on content related to nutrition education in textbooks of school policies on nutrition and health. This study aimed to evaluate the nutrition education on senior high schools in Mamuju Regency.Methods: This qualitative study examined word by word of high school students textbooks’ content of nutrition and health education. The main study material was textbooks used by high school students in Mamuju Regency. The research informants were students and teachers. The analysis was done through content analysis by examining words and pictures in the textbooks. Data was classified into the same categories to answer the research objectives.Results: Only a small proportion of textbooks (0.17%) contain nutrition and health messages. The nutrition and health messages included the nutritional content of food, food labels, and physical activity such as how to do long jump. Informants did not get information on adolescent health and nutrition at school. In addition, there is currently no school policy regarding breakfast or healthy snacks in the school environment.Conclusion: Balanced nutrition messages had not been published in textbooks and delivered regularly in schools. Policy makers should review the school curriculum to include nutrition and health messages for adolescents in the textbooks used.